Antioxidation Mechanisms of Catechin, Epicatechin and Quercetin Using Linear Solvation Energy Relationship - Jin, Y.; Cheng, Y.D.; Row, K.H.; Jin, Y.S.; Xuan, Y.H.; Jin, M.J. (Asian Journal of Chemistry, 2013)
The fundamental chemical interactions governing the anti-oxidations such as ferric reducing power (FRAP) assay, two methods based on the ability to scavenge the ABTS•+ radical cation, scavenging of the stable DPPH* radical and of authentic peroxynitrite (ONOO–) of three polyphenols such as catechin, epicatechin and quercetin were investigated using linear solvation energy relationship (LSER) model. The ability of the LSER to account for the chemical interactions underlying polyphenols antioxidation was shown. A comparison of predicted and experimental antioxidation activities suggests that LSER formalism is able to reproduce adequately the experimental antioxidation activities of the three polyphenols studied in the different experimental conditions investigated. The predicted antioxidation activities by the LSER model have good agreement with experimental data in the employed conditions.